2020
DOI: 10.3390/cancers12082048
|View full text |Cite
|
Sign up to set email alerts
|

Telomeres and Telomerase in the Development of Liver Cancer

Abstract: Liver cancer is one of the most common cancer types worldwide and the fourth leading cause of cancer-related death. Liver carcinoma is distinguished by a high heterogeneity in pathogenesis, histopathology and biological behavior. Dysregulated signaling pathways and various gene mutations are frequent in hepatocellular carcinoma (HCC) and intrahepatic cholangiocarcinoma (iCCA), which represent the two most common types of liver tumors. Both tumor types are characterized by telomere shortening and reactivation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 164 publications
(265 reference statements)
2
34
0
Order By: Relevance
“…The prevalence of TERT promoter mutations was significantly different according to the underlying liver disease, with the highest frequency in HCV-related HCC (44%) followed by non-viral (38%) and HBV-related HCC (23%). The mutation rates were largely consistent with those in previous studies, which reported mutation frequencies of 50-60% in HCV-related and 25-35% in HBV-related HCCs [9][10][11]. Interestingly, we observed the more apparent association of TERT mutations with the prognosis of non-HBV HCC rather than HBV-related HCCs in the surgical group (Figure S2).…”
Section: Discussionsupporting
confidence: 91%
“…The prevalence of TERT promoter mutations was significantly different according to the underlying liver disease, with the highest frequency in HCV-related HCC (44%) followed by non-viral (38%) and HBV-related HCC (23%). The mutation rates were largely consistent with those in previous studies, which reported mutation frequencies of 50-60% in HCV-related and 25-35% in HBV-related HCCs [9][10][11]. Interestingly, we observed the more apparent association of TERT mutations with the prognosis of non-HBV HCC rather than HBV-related HCCs in the surgical group (Figure S2).…”
Section: Discussionsupporting
confidence: 91%
“…Understanding the biology and pathology of HCC is a challenge due to the cellular and anatomic complexities of the liver and the local immune environment [ 42 ], as well as due to high heterogeneity in pathogenesis, histopathology, and biological behavior [ 43 , 44 ]. There is an emerging body of literature that focuses on the role of tumor biology and microenvironment [ 30 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…A mutation in the promoter region of the TERT gene always occurs early during HCC oncogenesis and is regarded as a driver gene for HCC carcinogenesis [78]. The expression of mutational TERT genes results in telomeres extending compensates for eroded telomeric ends and allows for epithelial cell immortalization [79]. Frequent occurrences of TERT promoter mutations located at − 124 and − 146 bp relative to the start codon in various cancers, especially alterations in -124C > T, clearly boost transcriptional activity in HCC cell lines [80].…”
Section: Tertmentioning
confidence: 99%